Practice, knowledge and attitudes of physicians towards shared decision- making in their healthcare practice in the National scientific center of oncology and transplantology CF “UMC” in Astana, Kazakhstan: Pilot study - Mukhamedyarova, Meruyet (Nazarbayev University School of Medicine, 2018)
Despite the importance of shared decision-making in clinical practice, it is not widely implemented in health care systems in the world, including Kazakhstan. In order to develop an effective implementation strategy for shared decision-making to be practiced in hospitals in Kazakhstan, it is necessary to identify and understand physician’s knowledge, practices, attitudes and barriers towards shared decision-making.
Keywords: physicians; healthcare practice